ANALISIS PRICE DISCOUNT DAN PERCEIVED USEFULNESS TERHADAP MINAT PEMBELIAN ULANG MENGGUNAKAN FINTECH MELALUI INTERVENING CUSTOMERS SATISFACTION (Studi Kasus Pada Pengguna Aplikasi Gopay di Kota Yogyakarta) - Dika Prawita; Ambar Lukitaningsih; Henny Welsa (Universitas Sarjanawiyata Tamansiswa, 2021)
At present digital payment systems or electronic money have been widely used in Indonesia. Market share that is still wide open makes many fintech companies competing to provide discounts and various benefits of convenience when using the applications provided, one of which is GoPay. The purpose of this study is to analyze the effect of price discounts and perceived usefulness on repurchase interest using the GoPay application which is mediated by customer satisfaction variables. The data used in this study are primary data sourced from questionnaires, with a total sample of 84 respondents. The results of this study indicate that the price discount has a positive but not significant effect on customer satisfaction. Perceived usefulness have a positive and significant effect on customer satisfaction. Price discounts and perceived usefulness have a positive but not significant effect on repurchase intention. Customers satisfaction has a positive and significant effect on repurchase intention.Keywords : price discount, perceived usefulness, customers satisfaction, repurchase intention